Nuts, hexagonal, plain, normal height, normal across flats, with MJ threads, classifications. 600 MPa (at ambient temperature)/120°C, 600 MPa (at ambient temperature)/235°C, 900 MPa (at ambient temperature)/425°C, 1100 MPa (at ambient temperature)/235°C, 1100 MPa (at ambient temperature)/315°C, 1100 MPa (at ambient temperature)/650°C, 1210 MPa (at ambient temperature)/730°C, 1250 MPa (at ambient temperature)/235°C and 1550 MPa (at ambient temperature)/600°C. Dimensions. (15th November 1997) - British Standards Institution,
No abstract available